Observe o feixe de retas paralelas a seguir quais são os valores de x e y
Anexos:
![](https://pt-static.z-dn.net/files/d4e/0cd4ff1f9af79e078f99dfafec0f3405.jpeg)
Soluções para a tarefa
Respondido por
30
Teorema de Tales:
m/m = (x + 3)/(3x - 5)
(x + 3)/(3x - 5) = 1
3x - 5 = x + 3
3x - x = 5 + 3
2x = 8
x = 8/2
x = 4
m/m = (3x - 5)/(y + 1)
1 = (3 . 4 - 5)/(y + 1)
1 = 7/(y + 1)
y + 1 = 7
y = 7 - 1
y = 6
Respondido por
9
Resposta:
∧ ![\mathsf{\red{y = 6} } \mathsf{\red{y = 6} }](https://tex.z-dn.net/?f=+%5Cmathsf%7B%5Cred%7By+%3D+6%7D+%7D+)
Resolução passo-a-passo:
![\mathsf{\dfrac{x + 3}{3x - 5} = \dfrac{m}{m} } \\ \mathsf{\dfrac{x + 3}{3x - 5} = \dfrac{m}{m} } \\](https://tex.z-dn.net/?f=+%5Cmathsf%7B%5Cdfrac%7Bx+%2B+3%7D%7B3x+-+5%7D+%3D+%5Cdfrac%7Bm%7D%7Bm%7D+%7D+%5C%5C+)
![\mathsf{\dfrac{x + 3}{3x - 5} = 1 } \\ \mathsf{\dfrac{x + 3}{3x - 5} = 1 } \\](https://tex.z-dn.net/?f=+%5Cmathsf%7B%5Cdfrac%7Bx+%2B+3%7D%7B3x+-+5%7D+%3D+1+%7D+%5C%5C+)
![\mathsf{{x + 3} = 1 ({3x - 5})} \\ \mathsf{{x + 3} = 1 ({3x - 5})} \\](https://tex.z-dn.net/?f=+%5Cmathsf%7B%7Bx+%2B+3%7D+%3D+1+%28%7B3x+-+5%7D%29%7D+%5C%5C+)
![\mathsf{{x + 3} = {3x - 5}} \\ \mathsf{{x + 3} = {3x - 5}} \\](https://tex.z-dn.net/?f=+%5Cmathsf%7B%7Bx+%2B+3%7D+%3D+%7B3x+-+5%7D%7D+%5C%5C+)
![\mathsf{3x - x = 3 + 5} \\ \mathsf{3x - x = 3 + 5} \\](https://tex.z-dn.net/?f=+%5Cmathsf%7B3x+-+x+%3D+3+%2B+5%7D+%5C%5C+)
![\mathsf{2x = 8} \mathsf{2x = 8}](https://tex.z-dn.net/?f=+%5Cmathsf%7B2x+%3D+8%7D+)
![\mathsf{\green{x = 4} } \mathsf{\green{x = 4} }](https://tex.z-dn.net/?f=+%5Cmathsf%7B%5Cgreen%7Bx+%3D+4%7D+%7D+)
![](https://tex.z-dn.net/?f=+)
![\mathsf{\dfrac{3x - 5}{y + 1} = \dfrac{m}{m} } \\ \mathsf{\dfrac{3x - 5}{y + 1} = \dfrac{m}{m} } \\](https://tex.z-dn.net/?f=+%5Cmathsf%7B%5Cdfrac%7B3x+-+5%7D%7By+%2B+1%7D+%3D+%5Cdfrac%7Bm%7D%7Bm%7D+%7D+%5C%5C+)
![\mathsf{\dfrac{3 \cdot 4 - 5}{y + 1} = 1 } \\ \mathsf{\dfrac{3 \cdot 4 - 5}{y + 1} = 1 } \\](https://tex.z-dn.net/?f=+%5Cmathsf%7B%5Cdfrac%7B3+%5Ccdot+4+-+5%7D%7By+%2B+1%7D+%3D+1+%7D+%5C%5C+)
![\mathsf{2 - 5= 1 (y + 1)} \\ \mathsf{2 - 5= 1 (y + 1)} \\](https://tex.z-dn.net/?f=+%5Cmathsf%7B2+-+5%3D+1+%28y+%2B+1%29%7D+%5C%5C+)
![\mathsf{ 7 = {y + 1}} \\ \mathsf{ 7 = {y + 1}} \\](https://tex.z-dn.net/?f=+%5Cmathsf%7B+7+%3D+%7By+%2B+1%7D%7D+%5C%5C+)
![\mathsf{y = 7 - 1} \\ \mathsf{y = 7 - 1} \\](https://tex.z-dn.net/?f=+%5Cmathsf%7By+%3D+7+-+1%7D+%5C%5C+)
![\mathsf{\red{y = 6} } \mathsf{\red{y = 6} }](https://tex.z-dn.net/?f=+%5Cmathsf%7B%5Cred%7By+%3D+6%7D+%7D+)
Boa interpretação :)
Resolução passo-a-passo:
Boa interpretação :)
Perguntas interessantes
Geografia,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
10 meses atrás
História,
1 ano atrás